2013
DOI: 10.1590/0103-6440201302168
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin and Fibronectin Expression after Pulp Capping with Different Hemostatic Agents: A Preliminary Study

Abstract: This study investigated the expression of extracellular matrix glycoproteins tenascin (TN) and fibronectin (FN) in pulp repair after capping with calcium hydroxide (CH), following different hemostasis protocols. Class I cavities with a pulp exposure were prepared in 42 human third molars scheduled for extraction. Different hemostatic agents (0.9% saline solution, 5.25% sodium hypochlorite and 2% chlorhexidine digluconate) were used and pulps were capped with CH cement. After 7, 30 or 90 days, teeth were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
7
0
4
Order By: Relevance
“…A clinical trial investigated different methods of attaining haemostasis using either saline, NaOCl or chlorhexidine digluconate, prior to pulp capping with Ca(OH) 2 (Baldissera et al . ). It was shown that the various approaches did not affect the expression of bioactive glycoproteins related to repair (Baldissera et al .…”
Section: Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…A clinical trial investigated different methods of attaining haemostasis using either saline, NaOCl or chlorhexidine digluconate, prior to pulp capping with Ca(OH) 2 (Baldissera et al . ). It was shown that the various approaches did not affect the expression of bioactive glycoproteins related to repair (Baldissera et al .…”
Section: Reviewmentioning
confidence: 97%
“…It was shown that the various approaches did not affect the expression of bioactive glycoproteins related to repair (Baldissera et al . ). Furthermore, a randomized clinical trial has reported improved outcomes, if a disinfection agent such as NaOCl is applied the haemostatic protocol prior the application of a capping material (Tuzuner et al .…”
Section: Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…After differentiation, they are no longer able to multiply, which limits the regenerative capability of the pulp (1,2). Damage to dental pulp induces inflammatory responses with different degrees, corresponding to the nature and strength of injury (2). In pathological conditions, such as mild carious dentine lesions, odontoblastic activity is stimulated to elaborate reactionary dentine (3).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is an additional challenge to obtain an appropriated apical seal in IPT by applying CET (6). Currently, necrosed immature permanent teeth are subjected to multiple-visit apexification with Ca(OH) 2 -based materials to induce formation of an apical mineralized barrier (6,7). Despite the good prognosis, the long-term Ca(OH) 2 -based apexification presents a series of drawbacks (8), such as multiple treatment appointments, probable recontamination of the root canal system during treatment and increased brittleness of the root dentin, which increases the risk of future cervical root fractures (7).…”
Section: Introductionmentioning
confidence: 99%